(untitled) (Progressive Agriculture, 2013)
A laboratory based 2 × 2 factorial experiment was conducted to investigate the effects of dietary phosphorus and zinc levels on hematocrit value, plasma alkaline phosphatase activity and plasma mineral contents of rainbow trout fingerling for 21 weeks. Two levels of phosphorus (19 and 30 mg/g) and two levels of zinc (55 and 100 µg/g) in the dry diets were tested. Duplicate tanks of 30 rainbow trout (average weight 1.56 ± 0.24g) per 60L glass tank were fed experimental diets three times a day to satiation level in 15 to 24oC water temperature. Zinc supplementation in the practical diets significantly increased the hematocrit value, plasma alkaline phosphatase activity and plasma zinc contents in rainbow trout fingerling. On the other hand, addition of phosphorus did not show any significant difference among the treatments. The result of the present study demonstrated that additional zinc significantly (P<0.05) influenced the hematocrit value, plasma alkaline phosphatase activity and plasma zinc contents in rainbow trout. Hence, it can be concluded that zinc supplementation is necessary in fingerling rainbow trout feed. Further studies in this area with different size and age of rainbow trout are needed broadly. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16870 Progress. Agric. 20(1 & 2): 183 192, 2009